Increased motor-impairing effects of the neuroactive steroid sregnanolone in mice with targeted inactivation of the GABA(A) seceptor gamma 2 subunit in the cerebellum - Leppa,E; Linden,A-M; Aller,MI; Wulff,P; Vekovischeva,O; Luscher,B; Lueddens,H; Wisden,W; Korpi,ER (Frontiers in Pharmacology, 2016)
Endogenous neurosteroids and neuroactive steroids have potent and widespread actions on the brain via inhibitory GABAA receptors. In recombinant receptors and genetic mouse models their actions depend on the α, β, and δ subunits of the receptor, especially on those that form extrasynaptic GABAA receptors responsible for non-synaptic (tonic) inhibition, but they also act on synaptically enriched γ2 subunit-containing receptors and even on αβ binary receptors. Here we tested whether behavioral sensitivity to the neuroactive steroid agonist 5β-pregnan-3α-ol-20-one is altered in genetically engineered mouse models that have deficient GABAA receptor-mediated synaptic inhibition in selected neuronal populations. Mouse lines with the GABAA receptor γ2 subunit gene selectively deleted either in parvalbumin-containing cells (including cerebellar Purkinje cells), cerebellar granule cells, or just in cerebellar Purkinje cells were trained on the accelerated rotating rod and then tested for motor impairment after cumulative intraperitoneal dosing of 5β-pregnan-3α-ol-20-one. Motor-impairing effects of 5β-pregnan-3α-ol-20-one were strongly increased in all three mouse models in which γ2 subunit-dependent synaptic GABAA responses in cerebellar neurons were genetically abolished. Furthermore, rescue of postsynaptic GABAA receptors in Purkinje cells normalized the effect of the steroid. Anxiolytic/explorative effects of the steroid in elevated plus maze and light:dark exploration tests in mice with Purkinje cell γ2 subunit inactivation were similar to those in control mice. The results suggest that, when the deletion of γ2 subunit has removed synaptic GABAA receptors from the specific cerebellar neuronal populations, the effects of neuroactive steroids solely on extrasynaptic αβ or αβδ receptors lead to enhanced changes in the cerebellum-generated behavior.